EFEKTIVITAS AUDIT INTERNAL : DIPENGARUHI OLEH FAKTOR INDEPENDEN, KEMAHIRAN PROFESIONAL, KOMUNIKASI DAN DUKUNGAN TOP MANAJEMEN: THE EFFECTIVENESS OF INTERNAL AUDIT: AFFECTED BY INDEPENDENT FACTORS, PROFESSIONAL SKILLS, COMMUNICATION AND TOP MANAGEMENT SUPPORT - Syahrul Syahrul; Andreas Andreas; M Rasuli (CURRENT: Jurnal Kajian Akuntansi dan Bisnis Terkini, 2023)
This Research is conducted on factors that affect the effectiveness of internal audit. This Researchers used a questionnaire with 43 questions for 203 respondents. Data analyzed using SEM-PLS – WarpPLS. Factors affecting the effectiveness of internal audit include independence, professional proficiency, communication, and management support. Internal audit can access all company data for independent examination. All auditors use their professional expertise to analyze a problem and provide suggestions for improvement and provide more value for the company. Communication is important for the examiner from the beginning of the inspection planning to the creation of the report. Top Management support is needed to support the achievement of company inspection objectives.